Tuning the acidic properties of aluminas via sol-gel synthesis: New findings on the active site of alumina-catalyzed epoxidation with hydrogen peroxide - Rinaldi, Roberto; Fujiwara, Fred Y.; Holderich, Wolfgang; Schuchardt, Ulf (Elsevier B.V., 2006)
This study answers several pending questions about alumina-catalyzed epoxidation with aqueous 70 wt% H2O2. To evaluate the effect of the water-to-aluminum tri-sec-butoxide molar ratio, this was systematically changed from 1 to 24. The xerogels were calcined at 450 degrees C and gave different gamma-Al2O3's with distinct textural and acidic properties. A combination of Al-27 MAS NMR and TPD-NH3 results of calcined aluminas allowed us to assign the type la. Al-OH sites as the catalytic sites for epoxidation. The type Ib Al-OH sites have no function in catalytic epoxidation, because ethyl acetate poisons these sites. The strong acid sites of types IIa, IIb, and III Al-OH groups are responsible for the undesired H2O2 decomposition and decreased oxidant selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: sol-gel alumina; catalytic epoxidation; hydrogen peroxide